Emotions of the ostomy patients due to colorectal cancer in the nursing care practice - Wiraszka, Grażyna (Polish Journal of Public Health, 2010)
Aim. The purpose of the research was the assessment of the emotions of patients with stoma resulting from the surgical treatment of colorectal cancer and the analysis of its social-demographic conditions.Material and the applied methods.  A standardized FACT-C form (Functional Assessment of Cancer Therapy Scale – Colorectal) and the HADS (Hospital Anxiety and Depression Scale) were used. The research was carried out on 164 patients at the Świętokrzyskie Oncology Centre in Kielce. The control group was also used for the purpose of the research.Results. The emotional condition of the patients was really worse in comparison with the control group, considering the evaluation made in the  EWB scale of the FACT-C questionnaire (p